Fluorescent competitive assay for melamine using dummy molecularly imprinted polymers as antibody mimics - Xin-wei DU; Yan-xin ZHANG; Yong-xin SHE; Guang-yang LIU; Feng-nian ZHAO; Jing WANG; Shan-shan WANG; Fen JIN; Hua SHAO; Mao-jun JIN; Lu-fei ZHENG (Journal of Integrative Agriculture)
A fluorescent competitive assay for melamine was first developed utilizing dummy molecularly imprinted polymers (DMIPs) as artificial antibodies. This method is based on the competition between fluorescent substances and the unlabeled analyte for binding sites in synthesized DMIPs and the decreased binding of fluorescent substances to DMIPs due to increased concentrations of melamine in the solutions. DMIPs for melamine were synthesized under a hot water bath in the presence of the initiator azobisisobutyronitrile (AIBN) using 2,4-diamino-6-methyl-1,3,5-triazine (DAMT) as a dummy template, methacrylic acid (MAA) as a functional monomer, and ethylene glycol dimethacrylate (EGDMA) as a crosslinking agent. The adsorption capacity and selectivity of DMIPs for melamine were evaluated by the isothermal adsorption curve and Scatchard analysis. The evaluation results showed that the synthesized DMIPs had specific recognition sites for melamine and the maximum adsorption amount was 1 066.33 μg g−1. Later, 5-(4,6-dichlorotriazinyl) amino fluorescein (DTAF) with a triazine ring, which slightly resembles melamine, was selected as the fluorescent substance. The fluorescent competitive assay using DMIPs as the antibody mimics was finally established by selecting and optimizing the reaction solvents, DMIPs amount, DTAF concentration, and incubation time. The optimal detection system showed a linear response within range of 0.05–40 mg L−1 and the limit of detection (LOD) was 1.23 μg L−1. It was successfully applied to the detection of melamine in spiked milk samples with satisfactory recoveries (71.9 to 86.3%). According to the comparative analysis, the result of optimized fluorescent competitive assay revealed excellent agreement with the HPLC-MS/MS result for melamine.